The heart of the war in Colombia - Ardila Galvis, Constanza (Latin American Bureau, 2000)
"Colombia is in the grip of the longest running civil war in Latin America. Thousands are killed each year, and one-and-a-half million have already been internally displaced. The guerrilla have a presence in half the country's municipalities, the armed forces are the recipients of massive US military aid and the paramilitarities have the capacity to inflict the highest number of casualties of all." "The question raised by The Heart of the War is universal: how do people face the truth of trauma to work for a better future? This is a people's history, where the collective memory of injustice and violence calls out not for revenge, but for peace."--Jacket